Pendampingan Pembentukan Paket Wisata Berkelanjutan Pada Kelompok Sadar Wisata Desa Mertak Kecamatan Pujut - Rusdan Rusdan; Handayani Rinuastuti; Rahman Dayani (Jurnal Gema Ngabdi, 2020)
One approach to developing tourism that involves the active participation of local communities is the development of Tourism Villages. Mertak Village with Gunung Tunaknya Nature Tourism Park (TWA) is a village that is very well known as one of the natural tourist destinations on the island of Lombok. The tourism potentials of Mertak Village are relatively many, especially those that utilize nature as its main means, but each of the potential tourism objects is developed partially and has not been integrated with other tourism potentials, tourists have not yet fully received a memorable experience. This service is focused on Mertak Village Pokdarwis, which aims to; (a) Increase creativity, (b) Increase tourism insight, (c) Improve Entrepreneurial Soul, (d) Encourage to apply good or positive business rules in serving tourists. The problem solving method used is; (a) Conducting focus group discussions (FGD), (b) Observation of the potential of Gunung Tunak TWA, (c) Assistance in preparing tour packages, (d) training in sustainable tourism and tourism business management. As a result of the activity, participants gained knowledge and guidance on sustainable tourism management and tourism business management, as well as the formation of several tour packages at TWA Gunung Tunak.